Identifikasi Bentuk Tekanan Ekonomi Petani Transmigran Jawa di Desa Langgea Kecamatan Abuki Kabupaten Konawe - Ashmarita Ashmarita; Nur Atia; Abdul Jalil; Rameon Renggala; Marsia Sumule G (Jurnal Agrimanex: Agribusiness, Rural Management, and Development Extension, 2021)
The purpose of this study is to determine the forms of economic pressure for Javanese transmigrant farmers in Langgea Village, Abuki District, Konawe Regency. This research is descriptive qualitative. Data collection techniques were carried out by means of observation and interviews. The results showed that Javanese transmigrant farmers experienced economic pressures, especially since the government issued a regulation on limiting the amount of fertilizer for farmers which had implications for decreasing their agricultural production. In addition, farmers have to pay high operational costs from planting to harvesting and economic pressure from banks that lend capital to buy production tools and the payment due date is after the harvest season.